Survey on Improved Privacy Preserving in Peer-to-Peer Multimedia Distribution - N.S, Sajna.; R.Das, Annie. (IJRDO -Journal of Computer Science Engineering, 2016)
The rapid popularity of network-based multimedia applications poses many challenges for multimedia content providers to provide efficient multimedia services. Recently, there are many research interests in providing efficient and scalable multimedia distribution service. When selling electronic content, the merchant would like each buyer to receive a same copy of the content fingerprinted with different serial number, in order to be able to trace redistributors should illegal redistribution happen. Fingerprinting schemes used to detect illegal redistributing multimedia data by enabling the original merchant of the multimedia data to identify the original buyer of a redistributed copy. Anonymous fingerprinting is a convenient solution for the legal distribution of multimedia contents with copyright protection while preserving the privacy of original buyers, whose identities are only revealed in case of illegal re-distribution happens